Inulin: properties and health benefits - Qin, Yu-Qing; Wang, Liu-Yan; Yang, Xin-Yu; Xu, Yi-Jie; Fan, Gang; Fan, Yan-Ge; Ren, Jing-Nan; An, Qi; Li, Xiao (Food & function, 2023)
Inulin, a soluble dietary fiber, is widely found in more than 36 000 plant species as a reserve polysaccharide. The primary sources of inulin, include Jerusalem artichoke, chicory, onion, garlic, barley, and dahlia, among which Jerusalem artichoke tubers and chicory roots are often used as raw materials for inulin production in the food industry. It is universally acknowledged that inulin as a prebiotic has an outstanding effect on the regulation of intestinal microbiota via stimulating the growth of beneficial bacteria. In addition, inulin also exhibits excellent health benefits in regulating lipid metabolism, weight loss, lowering blood sugar, inhibiting the expression of inflammatory factors, reducing the risk of colon cancer, enhancing mineral absorption, improving constipation, and relieving depression. In this review paper, we attempt to present an exhaustive overview of the function and health benefits of inulin. Inulin shows great health benefits in regulating gut flora, regulating glycolipid metabolism, weight loss, anti-inflammatory, reducing the risk of colon cancer, enhancing mineral absorption, improving constipation, and relieving depression.